Is 3D-printed Titanium cage a reliable option for 3-level anterior cervical discectomy and fusion in treating degenerative cervical spondylosis? - Wang, Shanxi; Fang, Xuan; Qu, Yunkun; Lu, Rui; Yu, Xiaojun; Jing, Shaoze; Ding, Qing; Liu, Chaoxu; Wu, Hua; Liu, Yang (Frontiers in Surgery, 2023)
Background: To assess the clinical and radiographical outcomes of 3-level anterior cervical discectomy and fusion (ACDF) with a 3D-printed titanium cage in treating degenerative cervical spondylosis. Methods: In this study, 25 patients with degenerative cervical spondylosis who underwent 3-level ACDF using a 3D-printed titanium cage from March 2019 to June 2021 were retrospectively enrolled. The patient-reported outcome measures (PROMs) were evaluated by visual analog scale (VAS) for the neck (VAS-neck) and arm pain (VAS-arm), Neck Disability Index (NDI) score, Japanese Orthopedic Association (JOA) score, SF-12 concise health survey, and the Odom criteria. The radiographical parameters, including C2-C7 lordosis, segmental angle, segmental height, and subsidence, were assessed. The mean duration of follow-up was 25.6 months. Results: Bony fusion was achieved in all patients (100%). In three patients (12%) mild dysphagia was observed during the follow-up. The VAS-neck, VAS-arm, NDI score, JOA score, SF-12 score, C2-C7 lordosis, and segmental angle improved noticeably at the latest follow-up. Based on the Odom criteria, 22 patients (88%) reported satisfactory (excellent or good). The mean loss of C2-C7 lordosis and segmental angle between the immediate postoperative and the latest follow-up values were 1.6° ± 0.5° and 1.1° ± 0.5°, respectively. The mean subsidence was 0.9 ± 0.6 mm. Conclusion: In patients with multi-level degenerative cervical spondylosis, 3-level ACDF using the 3D-printed titanium cage can effectively relieve the symptoms, stabilize the spine, and restore segmental height and cervical curvature. It is proven to be a reliable option for patients with 3-level degenerative cervical spondylosis. However, a future comparative study involving a larger population and longer follow-up time may be required to further evaluate the safety, efficacy and outcomes of our preliminary results.